Tombs of the South Asasif necropolis Thebes, Karakhamun (TT 223), and Karabasken (TT 391) in the twenty-fifth dynasty - Booth, Adam; Budka, Julia 1977-; Eigner, Dieter; Griffin, Kenneth; Ikram, Salima 1965-; Josephson, Jack A. 1930-; Molinero Polo, Miguel Ángel; Morkot, Robert; Naunton, Chris 1978-; Szpakowska, Kasia Maria (The American University in Cairo Press, 2014)
This volume is a joint publication of the members of the American-Egyptian mission South Asasif Conservation Project, working under the auspices of the State Ministry for Antiquities and Supreme Council of Antiquities, and directed by the editor. The Project is dedicated to the clearing, restoration, and reconstruction of the tombs of Karabasken (TT 391) and Karakhamun (TT 223) of the Twenty-fifth Dynasty, and the tomb of Irtieru (TT 390) of the Twenty-sixth Dynasty, on the West Bank of Luxor. These tombs, located in the South Asasif necropolis, were considered almost completely ruined by floods and constant re-usage. Therefore, when the project was initiated in 2006, the team was uncertain of the condition of the tombs and the amount of original material still remaining in the ruins and debris. The results of the first few years of work surpassed the most optimistic prognoses, of which there were not many. The tombs, as damaged as they are, have proved to be reconstructible, based on the thousands of fragments of the original decoration found during the clearing of the remains of the architectural features
A joint publication of the members of the American-Egyptian South Asasif Conservation Project (SACP), working under the auspices of the Ministry of State for Antiquities and the Supreme Council of Antiquities. - Includes bibliographical references (pages 271-290)
Introduction -- The history and monuments of Thebes in the Kushite period ; Thebes under the Kushites / Robert G. Morkot -- Royal sculpture at the onset of the twenty-fifth dynasty / Jack A. Josephson -- The South Asasif necropolis ; The history of the South Asasif necropolis and its exploration / Elena Pischikova -- Style and iconography of the decoration in the tombs of Karabasken and Karakhamun : archaism and innovations / Elena Pischikova -- Ground penetrating radar survey of the South Asasif necropolis / Adam Booth and Kasia Szpakowska -- The tomb of Karakhamun (TT 223) ; Titles of Karakhamun and the Kushite administration of Thebes / Christopher Naunton -- Karakhamun revisited : some remarks on the architecture of TT 223 / Dieter Eigner -- Vestibule : daily-life scenes in the tomb of Karakhamun / Elena Pischikova -- The textual program of Karakhamun's first pillared hall / Miguel Ángel Molinero Polo -- The 'Book of the Dead' from the second pillared hall of the tomb of Karakhamun : a preliminary survey / Kenneth Griffin -- A bright night sky over Karakhamun : the astronomical ceiling of the main burial chamber in TT 223 / Miguel Ángel Molinero Polo -- Preliminary notes on coffin fragments discovered in TT 223 / John H. Taylor -- Pottery from the tomb of Karakhamun (TT 223) / Julia Budka -- A preliminary note on the faunal remains from the South Asasif Conservation Project / Salima Ikram
Keywords: Geschichte 1000 v. Chr.600 v. Chr.; HISTORY / Ancient / Egypt / bisacsh; SOCIAL SCIENCE / Archaeology / bisacsh; Antiquities / fast / (OCoLC)fst00810745; Tombs / fast / (OCoLC)fst01152439; Tombs -- Egypt -- Thebes (Extinct city); Funde; Grab; Egypt / Al ʻAsāsīf / fast / (OCoLC)fst01882639; Egypt / Thebes (Extinct city) / fast / (OCoLC)fst01897333; Thebes (Egypt : Extinct city) -- Antiquities; Al ʻAsāsīf (Egypt) -- Antiquities; Asasif; Aufsatzsammlung